Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content 1. The validity of evidence derived from invalid procedures (A foundational study) Dr. Badr Fahd Hndi Aljohani 2. Arbitration Agreement Provisions in Oil Franchise Contracts Disputes - Comparative Study – Upon Application to GCC Countries Dr. Fadwa Mohammed Ali Badwi 3. Judicial Immunity of Diplomatic Missions Mrs. Abrar Jamal Alamoudi 4. Activating the developmental social role of the Social Solidarity Fund at King Saud University )Proposed template( Mrs. Deem Saleem Alotiby 5. The inflation function in the Sudanese economy for the period (1992-2022) Ebtihag Hashim Mohammed Algzoli 6. The Reality of Using Digital Platforms and their Impact on Achieving Social Solidarity, the (Ehsan) Platform as a Model Prof. Fahad Mohammed Abed 7. Internal Marketing and Anti-Productive Work Behaviors (Relationship and Effect): An Applied Study at Taif University Prof. Kholoud Ragheb Alqutub